2000
DOI: 10.1177/0193723500244007
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as a Normalizing Experience for School-Age Children with Physical Disabilities

Abstract: Children with physical disabilities are frequently excluded by classmates and discouraged from participating in such typical childhood experiences as physical activity. By being restricted from this context, these children have fewer opportunities to enhance physical and social skills. The purpose of this study is to examine the socialization potential of physical activity for children with physical disabilities. In-depth, tape-recorded interviews were conducted with 21 boys and girls with physical disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…Individuals at this developmental age, who are visibly different in some aspects, are at risk of developing a poor self-image, and especially a low satisfaction with themselves [28]. For pre-adolescents and adolescents, physical appearance is strongly related to their overall self-image [23], which has also been supported by our results showing that negative physical self dominates the overal self-image.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Individuals at this developmental age, who are visibly different in some aspects, are at risk of developing a poor self-image, and especially a low satisfaction with themselves [28]. For pre-adolescents and adolescents, physical appearance is strongly related to their overall self-image [23], which has also been supported by our results showing that negative physical self dominates the overal self-image.…”
Section: Discussionsupporting
confidence: 80%
“…Primarily, they have a deteriorated image of their physical self, which they clearly link to their skin symptoms. It is understandable that at the pre-adolescent and adolescent age it is very important to fit in and look beautiful according to the proclaimed standards of beauty [21,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…22 But participation provides opportunities for socialization and skill development, and helps to demonstrate one's abilities to others. 23 Participating in relatively few active physical activities may deny children those opportunities. As highlighted by Law et al, 1 the lack of participation in physical activity raises concerns about the children's long-term health and fitness.…”
Section: Discussionmentioning
confidence: 99%
“…I would have had to creep or something; it wouldn't have worked. (Kent 17 years) Previous research has pointed out that children and young people with disabilities are excluded from sport due to factors that can be related to the disability in itself and to the need for help and support that it implies (Taub & Greer, 2000;Vickerman et al, 2003). As the interviewees confirmed, the time required for treatment and care and transportation difficulties are real obstacles to taking part in sport.…”
Section: (Daniel 16 Years)mentioning
confidence: 96%
“…In addition, they have generally fewer opportunities to participate due to physical, social and emotional barriers. Their experiences are often limited due to the lack of necessary skills, overprotective adults, social isolation, time-consuming treatment and care, and difficulties in getting to and from training and matches (Taub & Greer, 2000). Additionally, previous studies have shown that mobbing and isolation, inaccessible premises, lack of sports aids and few individually adapted activities contribute to negative experiences and exclusion (Coates & Vickerman, 2010).…”
Section: Introductionmentioning
confidence: 99%